Family placement of the enigmatic Otagia neozelanica (Chilton, 1897) Haustorioidea: Otagiidae fam. nov. (Amphipoda: Crustacea) - Hughes, Lauren; Lörz, Anne-Nina (Zootaxa, 2013)
A neotype is designated for Otagia neozelanica (Chilton, 1897) and the new family Otagiidae is established for the mo-notypic genus Otagia. An assessment of the relationship of Otagiidae fam. nov. with the Haustorioidea families is pro-vided. The Otagiidae fam. nov. share a close relationship with seven other haustorioid families Cheidae, Condukiidae, Ipanemidae, Platyischnopidae, Phoxocephalopsidae, Sinurothoidae and Zobrachoidae.